A study of fracture in elastic-plastic material (epfm) - Le , Hiếu Giang; Nguyen , Lê Đăng Hải (Journal of Technical Education Science, 2012)
J integral was calculated based on Ramsberg Osgood stress-strain relationship at 200C for compact tension (CT) of 304 stainless steel for plane stress and plane strain when the ratio between crack length a and width of specimen W was changed. Besides the results, J was also calculated and simulated in the case of plane strain and plane stress with ANSYS. J values for the case of plane stress and plane strain were different. J values increased with the increase of the ratio between crack length a and width of specimen W and increased rapidly when the ratio was high (a/W=0,7)